Silica, a polimerized silicon dioxide, is widely used as raw materials for food industries, such as food packaging, filter agent, biomarkers and biosensor for various analysis. In biological sistem such as sponge, the formation of silica structure was directed by protein known as silicatein. The aims of this research were to extract silicatein-like protein isolated from sponge live surrounding the Nias and Lombok seacost Indonesia and to study their activity to polymerize tetraethoxyorthosilic - M.R.R. Lukie Trianawati; Maggy T. Suhartono; Dahrul Syah; Ekowati Chasanah (Forum Pasca Sarjana, 2008)
Silica, a polimerized silicon dioxide, is widely used as raw materials for food industries, such as food packaging, filter agent, biomarkers and biosensor for various analysis.  In biological sistem such as sponge, the formation of silica structure was directed by protein known as silicatein.  The aims of this research were to extract silicatein-like protein isolated from sponge live surrounding the Nias and Lombok seacost Indonesia and to study their activity to polymerize tetraethoxyorthosilicate (TEOS) in-vitro.  Protein in silica spicule was isolated by collecting silica spicule, soaked in HF/NH4F buffer (pH5.0) for dissolving silica and releasing this protein.  The protein was analysed by electrophoresis SDS-PAGE to estimate the molecular weight and the concentration was analyzed by Bradford method.  The highest yield of silica spicula was 58.5% of dry weight sponge that was isolated from sponge MT37.  By SDS-PAGE, the molecular weight of protein from N6 showed three bands of 32, 27, 23 kDa, while MT5 protein was 15.5 kDa, and MT37 protein was 18 kDa.  The highest polymerization activity was 144 µmol/ml TEOS occurs at 12 hours, showed by protein isolated from sponge MT37 of Lombok Marine.   Key words: sponge, silicatein like-protein, tetraethoxyorthosilicate